REGRESSION MODELS HEART RATE VARIABILITY DEPENDING ON THE CHARACTERISTICS OF THE BODY STRUCTURE, AGE AND POWER COMPRESSION OF HANDS IN HEALTHY YOUNG MEN AND WOMEN WITH HYPOKINETIC TYPE OF HEMODYNAMICS - Serheta, I.V.; Kovalchuk, V.V. (World of Medicine and Biology, 2015)
Aim of our work – to develop and conduct analysis of regression models individual regulatory parameters of HRV depending on the structural features and body size, age and strength performance compression of hands in boys and girls with hypokinetic type of hemodynamics.Materials and methodsTo determine the type of hemodynamics young men and women for 15 seconds was performed registration of tetrapolar chest rheogram sync with phonocardiogram and electrocardiogram. Type of circulation set by the value of cardiac index values. 62 almost healthy boys and 32 girls with hypokinetic type of hemodynamics recorded rhythmogram during recording electrocardiography in the second standard lead within 5 minutes followed by computer processing. In synchronization with electrocardiography using nasal thermistor recorded pneumogram. Data analysis of heart rate was performed using a computer program of certified cardiology diagnostic complex. As a result of the processing of the obtained results evaluated indicators of a variational pulsometry (mode - Mo; mode amplitude – AMo; the average value of R-R interval - NNM; minimum R-R interval - Min; maximum R-R interval - Max; variational sweep - VR), statistical (standard deviation length of normal RR intervals - SDNN; square root of the sum of squared difference of the quantities of successive pairs of normal RR intervals - RMSSD; percentage of pairs of successive normal RR intervals that differ more than 50 ms of the total number of consecutive pairs of intervals - PNN50) and spectral indicators of HRV (total power of recording in all ranges - FO; power in the range of very low frequency - VLF; power in the range of low frequency - LF; power in the range of high frequency - HF; related capacities in the range of low and high frequency - LF / HF) as recommended by the European and North American Heart Association (1996). Using the appropriate formulas calculated indicators of vegetative homeostasis by the method Baevsky, namely: vegetative balance index (IVR = AMo / VR); regulatory systems tension index (IN = AMo / (2 x VR x Mo)); vegetative index rate (VPR = 1 / (Mo x VR)).Anthropometric examination of boys was conducted in accordance with the scheme V.V. Bunak (1940). Definition of somatotype by method of J. Carter and B. Heath (1990). Definition component composition of body weight carried by the method of J. Matiegka (1921). Force compression of the right and left hand performed using a carpal dynamometer.To install individual normative parameters HRV depending on the characteristics of anthropo-somatotypological indicators, age and compression strength in the hands of boys and girls with different types of hemodynamic we used step method regression analysis in statistical package license "STATISTICA 5.5".Results. DiscussionsIn girls with hypokinetic type of hemodynamics built 15 models of parameters of HRV, and for 9 of them (PNN50, AMo, Max, Min, VR, VLF, LF, HF, LF/HF) coefficients of determination R2 equal to 0,504 (Max) to 0,798 (VLF); were not generally built models for SDNN and FO, and other indicators of HRV had accurate descriptions of signs from 9,9% (IN) to 42,7% (NNM). In boys with hypokinetic type of hemodynamics built 17 models of HRV parameters that have accurate descriptions of signs only from 0,097 (Min) to 0,403 (AMo).Most often to the models HRV indexes that were built included: in girls with hypokinetic type of hemodynamics - the width of distal epiphysis extremities (16.1o%, mainly upper extremity), the diameter of the body (13.1o%, mainly transverse sternum medium and sagittal size of chest and between the swivel pelvis size) and total body size (11.1o% due to weight and body surface area); and in boys with hypokinetic type of hemodynamics - the width of distal epiphysis extremities (26.5o%, mainly lower limb), compression strength of hands (17.6o% evenly on the left and right hand) and the diameter of the body (10.1o%, mainly between swivel size of the pelvis and sternum medium transverse and sagittal dimensions of the chest).
Keywords: healthy young men and women; heart rate variability; hemodynamics types; anthropometry; regression models